Teachers' attitudes towards the inclusion of children with special educational needs in Jordanian ordinary schools - Amaireh, Saleem (2017)
The purpose of this study is to investigate the attitudes of teachers towards inclusive education in Jordanian ‘ordinary’ schools. The first phase of the project reports questionnaire data from 367 teachers. Attitudes are examined in terms of three components: their beliefs and knowledge, feelings and behaviour. The results of the questionnaire revealed that ordinary teachers in Jordan hold relatively neutral views towards inclusive education. Several variables are found which relate to teachers’ attitudes; including training, experience of inclusive education and the type of disability.